Through the lens of self-construal: Cross-cultural variation in consumers' appreciation of harmony in marketing visuals. Issue 3 (14th May 2018) - Haberstroh, Kristina; Orth, Ulrich R.; Bouzdine-Chameeva, Tatiana; Cohen, Justin; Maria Corsi, Armando; Crouch, Roberta; De Marchi, Renata
Abstract : Purpose: Extending research on cultural differences in aesthetic appreciation, the purpose of this paper is to show how a more interdependent self-construal, a cultural and individual difference variable related to one's social self, impacts the influence of visual harmony on consumer evaluations of marketing artifacts' attractiveness. Design/methodology/approach: Data were obtained via three studies from a total of 1, 498 consumers in Australia, Brazil, China, France, Germany, and Italy. Marketing visuals included the design of products, packages, typefaces, and logos. Self-construal was both measured and manipulated. Findings: The results indicate that a person's self-construal moderates the effect of visual harmony on attractiveness. Specifically, the positive effect of visual harmony on attractiveness – through self-congruity – is more pronounced with consumers possessing a more interdependent self-construal, and with products that are more hedonic than utilitarian. Practical implications: Given the pivotal role attractiveness has in influencing consumer behavior, understanding what differences, at the individual and cultural levels, impact the harmony-attractiveness relationship helps marketers to better match the visual design of marketing stimuli to target audiences. Originality/value: This study is among the first to show how the social-self impacts consumer response to marketing visuals. Further, value stems from adopting a holistic perspective on design, clarifying the process mechanism, and identifying boundary conditions.